Digital Transformation of MSMEs through the Application of Generative AI in Branding Strategy - Baskara, Dominggo Bayu; Aditasari, Krisnayanti; Rahmadanti, Adisya Resti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This community service program aims to enhance the knowledge and skills of MSME actors in utilizing Generative Artificial Intelligence (Generative AI) to strengthen branding strategies in the digital era. The training was held offline on May 16, 2025, at Telkom University Surabaya Campus, attended by 25 MSMEs fostered by Telkom CDC Witel Suramadu. The implementation method adopted a learning by doing approach, focusing on prompt engineering using ChatGPT to produce product visuals, social media content calendars, and business slogans. Evaluation results show that participants found the material highly relevant to their needs (average score 4.63), easy to understand (4.56), and expressed strong interest in similar future programs (4.75). These findings indicate that hands-on training using a single AI platform can significantly improve MSMEs’ digital readiness, especially in marketing and visual communication. The program also fostered ethical awareness regarding AI use. This initiative contributes to community-based digital transformation and has strong potential for broader replication.